IMPLEMENTATION OF ISSUANCE OF LAND TITLE CERTIFICATES IN PEAT AREAS IN PEKANBARU CITY - Irwan; Irawan Harahap; Robert Libra (International Peneliti Ekonomi, Sosial dan Teknologi, 2026)
Land certificates are expected to guarantee legal certainty, protect community rights, while still paying attention to the ecological function of peat as part of the environment. The purpose of this study is to analyze the implementation, obstacles, and efforts to overcome obstacles in the issuance of land title certificates in peat areas in Pekanbaru City. The method used is sociological legal research. Based on the results of the study, it is known that the implementation of the issuance of land title certificates in peat areas in Pekanbaru City has not been carried out optimally, because the issuance of land title certificates in peat areas also has the potential to cause conflicts between the legal certainty of land rights and the interests of protecting the peat ecosystem if not accompanied by strict spatial use controls. Therefore, land certification in peat areas cannot be interpreted solely as legalization of land ownership, but must be placed within a conditional legal framework that takes into account the social function of land and environmental sustainability. Obstacles are complex and multidimensional in nature, including the unclear status and function of peat areas, which requires caution from land officials to avoid conflict with spatial planning and environmental protection provisions. Furthermore, the unstable physical condition of peatland causes difficulties in measuring and establishing boundaries, thus slowing the technical certification process. From an administrative and legal perspective, weak land rights, poorly documented land ownership histories, and overlapping land ownership claims are still common. This is exacerbated by the lengthy coordination process between agencies. Meanwhile, from the community perspective, obstacles also arise from a lack of understanding of land and environmental law, as well as minimal outreach and assistance, often making it difficult for applicants to meet the stipulated requirements.